Zoroastrian religion and the importance of the Bible “AVESTO” - Ibodov O`ktam Rasulovich (Zien Journals, 2022)
When the Zoroastrian religion, based on the belief of the only deity in Movarounnahr, Iran, Khorasan, was adopted, the construction of a special temple-ceasefire, in which the Ahura Mazda cult sanctuaries were located in the cities and villages of these territories, was in full swing
Keywords: National heritage; culture; art; ritual